Atomistic modulating of structural, elastic, and optoelectronic behavior of pure TiO2 and Fe/TiO2 for photoelectrochemical water splitting application - Junaid Khan; Matiullah Khan; Waqar Uddin; Paghunda; Fida Rehman; Abdul Hakim Shah; Atta Ur Rahman; Zeshan Ahmad (Results in Optics, 2024)
Titanium dioxide (TiO2) has attracted much attention because of their desirable physicochemical properties especially in the water splitting process. In this work pure and Fe-doped TiO2 compounds are studies theoretically with the help of Generalized Gradient Approximation with the revised Pardew–Burke–Ernzerh (RPBE) exchange–correlation scheme. Total Density of States (TDOS) and Partial Density of States (DOS) were analyzed in detail which show that iron (Fe) and oxygen (O) orbitals hybridize, especially in the region of the doping system conduction band minima for both modes. Additionally, this interaction produces an energy level that effectively reduces the bandgap of the adsorbed system. Optical properties were elucidated which shows that Fe-doped TiO2 system results in high absorption and photoconductivity. Moreover, the results demonstrate low bandgap energy which is suitable for the reduction in water splitting without the need for external energy. Magnetic properties demonstrated that Fe-doped TiO2 systems show very low diamagnetic responses. The calculated elastic properties of Fe-doped TiO2 indicate ductile nature of the material with a strong average bond strength. Fe-doped TiO2 exhibited less microcracks with a mechanically stable composition.